2020
DOI: 10.3892/ijmm.2020.4661
|View full text |Cite
|
Sign up to set email alerts
|

Ingenuity pathway analysis of differentially expressed genes involved in signaling pathways and molecular networks in RhoE gene‑edited cardiomyocytes

Abstract: RhoE/Rnd3 is an atypical member of the Rho superfamily of proteins, However, the global biological function profile of this protein remains unsolved. In the present study, a RhoE-knockout H9C2 cardiomyocyte cell line was established using cRISPR/Cas9 technology, following which differentially expressed genes (DEGs) between the knockout and wild-type cell lines were screened using whole genome expression gene chips. A total of 829 DEGs, including 417 upregulated and 412 downregulated, were identified using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The network of interaction between molecules, including genes, proteins chemicals, and drugs can be visualized in the experimental system. IPA uncovers the interaction and functional roles of the DEGs associated with the signaling pathways and their related disease and functions [ 33 ]. The disease and function classification given in Figure 3 C indicated that the DEGs are associated with the activation of cellular movement, immune cell trafficking, cell death and survival, cell cycle, cellular development, cellular growth and proliferation, cell to cell signaling, tissue development, connective tissue development, and hematological system development and function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The network of interaction between molecules, including genes, proteins chemicals, and drugs can be visualized in the experimental system. IPA uncovers the interaction and functional roles of the DEGs associated with the signaling pathways and their related disease and functions [ 33 ]. The disease and function classification given in Figure 3 C indicated that the DEGs are associated with the activation of cellular movement, immune cell trafficking, cell death and survival, cell cycle, cellular development, cellular growth and proliferation, cell to cell signaling, tissue development, connective tissue development, and hematological system development and function.…”
Section: Resultsmentioning
confidence: 99%
“…The IPA system is a QIAGEN’s bioinformatics pathway analytical tool ( (Accessed on 30 November 2021)) that uses a network generation algorithm to segment the network map of molecules into multiple networks and assign scores to each network [ 33 ]. For the canonical pathway, disease, and function analyses, a threshold of the Z-score of ≥2 was defined as significant activation, and a Z-score of ≤−2 was defined as significant inhibition [ 33 ]. Algorithms to calculate the overlap of Z-scores and p values were described previously [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…IPA is a robust and expertly curated database that can help to understand the characters of various molecules such as gene, protein, chemical substance, and drug and interaction network among the molecules [ 11 ]. The data from Mel.Rad mice were further analyzed by IPA to group the identified genes and locate the canonical pathways that the genes were involved in.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment of the focus genes in networks in IPA was assessed via Fisher's exact test. Furthermore, the software identifies top functions associated with each network via enrichment scores ( z -score), highlighting the predicted biological significance of the results [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%